MYUMRAH: A DIGITAL UMRAH MOBILE GUIDE APPLICATION - Aeni Zuhana Saidin; Nur Dania Mazlan (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Umrah, a sacred ritual in Islam, holds significant religious importance as believers seek to fulfill their faith. This article presents the development of the MyUmrah application, designed to assist pilgrims in their Umrah journey both before and during the performance of the ritual. This application encompasses various functions tailored to meet the needs of Umrah pilgrims. The development of MyUmrah follows an iterative application development process, beginning with the collection of data to establish requirements followed by design and development of the prototype that aligns with the identified requirements. To gain insights into the newly developed app, a prototype evaluation is conducted using dichotomous techniques, providing a comprehensive understanding of its functionality and effectiveness. The feedback received during the evaluation phase have been overwhelmingly positive, spanning various aspects of usefulness, usage, and design. This indicates a high level of acceptance and satisfaction among Umrah pilgrims. Users have reported positive experiences, affirming the application’s effectiveness in facilitating a smooth Umrah experience. MyUmrah application proves to be beneficial, offering valuable assistance to pilgrims throughout their sacred journey.